Effect of Metformin on Myocardial Injury Induced by Hepatic Ischemia-Reperfusion in Rats - Wen An; Ju-Seop Kang (Frontiers Media S.A., 2022)
Background: There is no effective medication for treatment or prevention of hepatic ischemia-reperfusion (HIR) injury caused by liver transplantation and hepatectomy. This study aimed to investigate the therapeutic effects of metformin on HIR injury and related myocardial injury in rats.Methods: Wistar male rats were randomly divided into four groups: sham group, ischemia-reperfusion group, and IR group treated with metformin 150 mg/kg and 100 mg/kg. Wistar male rats were administered metformin 150 mg/kg, 100 mg/kg or saline 30 min pre-operative and underwent 15 min ischemia and 6 h reperfusion (n = 4).Results: Metformin significantly alleviates the injury caused by HIR. Administration of metformin resulted in a significant reduction in the serum levels of alanine transaminase and aspartate transaminase and the activity of malondialdehyde, creatine kinase-MB, and lactate dehydrogenase but maintained high catalase and superoxide dismutase activity. Metformin significantly inhibited the IR-induced elevation of tumor necrosis factor-α in liver and heart tissue.Conclusion: Metformin can alleviate hepatic and myocardial injury induced by IR by inhibiting oxidative stress.